Factors associated with self-efficacy in patients with hypertension: a cross-sectional study from Palestine - Salam Khairy; Asala Aslan; Ahmad M. Samara; Ibrahim Mousa; Abdulsalam S. Alkaiyat; Sa'ed H. Zyoud (BMC, 2021)
Abstract Background Self-efficacy is a widely applied psychosocial concept that is commonly used in association with management of chronic diseases, including hypertension. The aim of this study was to assess self-efficacy of hypertension management and patient-physician communication, as well as the factors associated with self-efficacy and patient-physician communication among patients with hypertension in Palestine. Methods We conducted face-to-face, questionnaire-based interviews using validated instruments to assess self-efficacy in managing hypertension (Self-Efficacy for Managing Chronic Disease 6-Item Scale (SES6C)) and patient-physician communication (Perceived Efficacy in Patient-Physician Interaction Questionnaire (PEPPI)) in patients with hypertension at the three main primary healthcare centers in Nablus district in northern West Bank, Palestine. We also performed a multiple linear regression analysis to determine the variables independently associated with PEPPI and SES6C scores. Results We enrolled 377 participants with hypertension in this study. The average age (measured in years) was 56.8 with a standard deviation of 11.6. The mean PEPPI and SES6C scores were 20.0 (SD 4.4) and 41.1 (SD 10.6), respectively. In a multiple linear regression model, subjects who were city dwellers (B=3.597, p=0.004), and subjects with high education levels (B=4.010, p=0.001) achieved higher PEPPI scores, whereas subjects in the normal weight category (B=5.566, p<0.001) and those with higher PEPPI scores (B=0.706, p<0.001) achieved higher SES6C scores. Conclusions We found that impairment in self-efficacy was linked to overweight and obesity, as well as lower patient-physician communication. Moreover, our results showed that lower patient-physician communication was independently associated with low education level as well as non-city residency types. We recommend making the appropriate changes by both the policy-makers and the health care providers to improve the health facilities and its services, especially outside the cities. We also suggest holding specific counseling and training session on the management and control of hypertension.